2017
DOI: 10.1016/j.jclepro.2017.06.131
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted pyrolysis with chemical activation, an innovative method to convert orange peel into activated carbon with improved properties as dye adsorbent

Abstract: reactivation efficiency of AC. The recovery of AC with improved properties and the desirable process features (fast heating rate, short process time) suggest the great potential of this method as an alternative for the treatment and recovery of fruit peel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 232 publications
(55 citation statements)
references
References 54 publications
(72 reference statements)
3
41
0
1
Order By: Relevance
“…Biochar can be produced via pyrolysis of a variety of lignocellulose materials such as coconut shell, palm kernel shell, fruit peel, or rice straw . In particular, microwave pyrolysis is becoming a popular pyrolysis approach to produce biochar or activated carbon due to its several distinct advantages . Microwave radiation can provide a rapid and targeted heating effect to the material .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biochar can be produced via pyrolysis of a variety of lignocellulose materials such as coconut shell, palm kernel shell, fruit peel, or rice straw . In particular, microwave pyrolysis is becoming a popular pyrolysis approach to produce biochar or activated carbon due to its several distinct advantages . Microwave radiation can provide a rapid and targeted heating effect to the material .…”
Section: Introductionmentioning
confidence: 99%
“…16 In particular, microwave pyrolysis is becoming a popular pyrolysis approach to produce biochar or activated carbon 17 due to its several distinct advantages. [18][19][20][21] Microwave radiation can provide a rapid and targeted heating effect to the material. 18,20 This can be explained by the occurrence of dipole rotation and ionic conduction at the molecular level of the material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45] However, certain deciencies including costly, intricate pre-treatment and low adsorption capability limited the use of some certain adsorbents. [46][47][48][49][50][51][52][53] Due to the conjugated region, stacking structure and the weak forces of g-C 3 N 4 , it has the potential for aggregating functional groups or materials to form nanocomposite with multiform favorable properties. [54][55][56] This distinctive structure has drawn great interesting in improving the photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey showed that researchers have developed and used a wide variety of low-cost adsorbents for the removal of dyes. Some notable examples are almond shells, 18 Citrus limetta peel, 19 cottonseed hull, 20 Cucumis sativus peel, 21 egg shells, 22 eucalyptus bark, 23 Indian rosewood sawdust, 24 neem leaf powder, 25 mango seed, 26 orange peel, [27][28][29] peanut hull, 30 pomelo peel, 31,32 Psidium guajava leaf, 33 shaddock peel, 34 Terminalia arjuna sawdust, 35 Tectona grandis sawdust, 36 wheat bran, 37…”
Section: Introductionmentioning
confidence: 99%